Efficacy of Prophylactic Antibiotics in COPD: A Systematic Review - Anh Tuan Tran; Amr Sayed Ghanem; Marianna Móré; Attila Csaba Nagy; Ágnes Tóth (Antibiotics)
Background/Objectives: Chronic obstructive pulmonary disease (COPD) is a global health problem and the third leading contributor to mortality worldwide. This systematic review aims to summarize the results of previous studies tackling the question of the efficacy of long-term prophylaxis of antibiotics in COPD patients, with particular regard to exacerbation rate, time to first exacerbation, health status, airway bacterial load, inflammatory markers, cell counts in sputum samples, and potential adverse events. Results: Four studies found significant improvement in the exacerbation rate in patients receiving antibiotic intervention. One study found doxycycline to have negative effects on patients’ exacerbation outcomes. Two studies recorded a reduction in total airway bacterial load using quantitative culture of sputum samples, but the prevalence of antibiotic-resistant bacteria increased in all studies that measured it. No change in inflammatory markers was observed; however, there was a decline in neutrophil cell counts and, subsequently, reductions in neutrophil elastase concentrations. Methods: PubMed and Web of Science databases were searched for English-language studies presenting data on the prophylactic use of antibiotics in COPD management. All included studies are randomized controlled trials (RCTs) and meet the inclusion criteria. Conclusions: Based on current evidence from RCTs, the prophylactic antibiotic approach utilizing macrolides is the most effective in reducing the incidence of COPD exacerbation. However, the emergence of antibiotic-resistant pathogens is notable. Whether the beneficial effects of macrolides on exacerbation are due to their antibacterial or immunomodulant properties is still inconclusive. Future studies are needed to better understand the interactions between antibiotics and the airway microbiome during COPD exacerbation.